An analysis of different pole vaulting pole load-deformation testing regimes - Warburton, T.; James, R.; Lyttle, A.; Alderson, J. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This study aimed to determine whether differences in the pole elastic energy characterisation were evident between quasi-static and dynamic load-deformation testing on pole vault poles. A total of 12 pole vault poles were tested from three different manufacturers, who each utilise different materials within their pole construction processes. A quasi-static and a dynamic pole bending test was performed on each pole utilising a custom built rig. A 3D load cell was positioned in series with the rig to obtain the forces required to develop a load-deformation curve for each trial. The results of the bending trials demonstrate a noticeable difference in the load-deformation curves obtained via the two methods, most notably regarding the degree of hysteresis between the loading and unloading phases and the resultant elastic potential energy calculations.